2023
DOI: 10.3390/atmos14050861
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and Trends in Imotski, Croatia: An Analysis of Temperature and Precipitation

Abstract: This paper examines the long-term changes in temperature and precipitation in the karst region of Imotski, Croatia, which is of particular interest due to its abundance of karst phenomena. This study analyses temperatures and precipitation on monthly and annual scales at two climatological stations in the region, Imotski and Ričice. Linear regression, the Theil–Sen estimator (β), and the Mann–Kendall test were used to determine the trends and statistical significance. The homogeneity of the data was checked us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
3
1
0
Order By: Relevance
“…This finding corresponds with earlier studies that also reported high variations in rainfall over the Limpopo Province [27,49,50,81,82]. Similar variability in inter-annual rainfall was noted in studies conducted in Ethiopia and India [8,69]. In contrast, a study found a decreasing trend in rainfall in the Olifants catchment of South Africa [46].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding corresponds with earlier studies that also reported high variations in rainfall over the Limpopo Province [27,49,50,81,82]. Similar variability in inter-annual rainfall was noted in studies conducted in Ethiopia and India [8,69]. In contrast, a study found a decreasing trend in rainfall in the Olifants catchment of South Africa [46].…”
Section: Discussionsupporting
confidence: 90%
“…Various tests were employed to analyse climate parameters over the study period. To address the primary objective, statistical measures such as mean, standard deviation, and coefficient of variation [7,8,68,69] were calculated to assess both the annual and seasonal variability of rainfall, as well as minimum and maximum temperatures, spatially and temporally.…”
Section: Discussionmentioning
confidence: 99%
“…The MMK trends applied to the SPEI grid center point series seems to have some relation with the drought areal evolution and occurrence rate analysis, since the trend signals are predominantly significant in regions D1 and D2, showing more locations with significant negative trends compared to the few mainly non-significant positive trends that can be seen in region D3. In region D3, for both SPEI time-scales, the results seem to be in accordance with the results of [26] for the period 1960-2020, since for the mountainous system of the Dinarides, the authors identified a significant increase in precipitation due to the occurrence of very wet days using the daily intensity index, while the Imotski station (Southern Adriatic coast) detected a non-significant upward trend in the annual precipitation [56]. However, the effect of temperature on the aggravation of drought conditions seems to be less complex, since several authors show that statistically significant increases in air temperature, especially in the mean annual temperatures, consistently occurred all over the country in the last 50 years [57,58].…”
Section: Discussionsupporting
confidence: 84%
“…Also, a more intense and frequent occurrence of floods and droughts was observed (Trbić et al, 2018). Similar characteristics of the temperature rise have been recorded in all parts of Southeast Europe -for example in Serbia (Radivojević et al, 2015;Tošić et al, 2023), Croatia (Bonacci et al, 2021;Vrsalović et al, 2023;Ogrin, 2015), Slovenia (Ogrin, 2015;Tošić et al, 2016), Romania 2023), Хрвaтскoj (Bonacci et al, 2021;Vrsalović et al, 2023;Ogrin, 2015), Слoвeниjи (Ogrin, 2015;Tošić et al, 2016), Румуниjи (Bărbulescu, 2023;Birsan et al, 2014), Бугарској (Alexandrov et al, 2004), Бoсни и Хeрцeгoвини (Popov et al, 2018;Trbić et al, 2017), те Црнoj Гoри (Burić et al, 2014;Burić & Doderović, 2021;Doderović et al, 2020). Прoстoрнa и врeмeнскa (гoдишњa и сeзoнскa) хeтeрoгeнoст у рaспoдјeли пaдaвинa зaбиљeжeнa je у jугoистoчнoj Eврoпи, укључуjући Бoсну и Хeрцeгoвину (Popov et al, 2017), Србиjу (Luković et al, 2014;Milovanović et al, 2017;Milošević et al, 2021), Хрвaтску (Gajić-Čapka et al, 2015;Ogrin et al, 2022), Слoвeниjу (de Luis et al, 2014Milošević et al, 2016), Румуниjу (Dumitrescu et al, 2015;Croitoru et al, 2016), Бугарску (Bocheva et al, 2009;Nikolova, 2007), па и Црну Гoру (B...…”
Section: Introductionsupporting
confidence: 68%